2012
DOI: 10.5194/isprsarchives-xxxix-b8-317-2012
|View full text |Cite
|
Sign up to set email alerts
|

Ndvi From Active Optical Sensors as a Measure of Canopy Cover and Biomass

Abstract: ABSTRACT:Commercially available proximal sensors are being used in precision agriculture to provide non-destructive, real-time spatial information on 'green biomass' that may be of interest to the remote sensing community. The sensors are described as biomass sensors, but questions remain on which canopy characteristics can be best estimated by the sensor measurements. In this study Normalized Difference Vegetation Index (NDVI) measurements from active optical sensors were examined across multiple datasets, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Non-destructive measurements of canopy reflectance, from which Normalised Difference Vegetation Index (NDVI) was calculated, were taken with a CropCircle ACS-210 with GeoSCOUT GLS-400 data logger (Holland Scientific, Lincoln, NE, USA) as an indirect measurement of crop canopy development (Fitzgerald, 2010;Perry et al, 2012). These were taken approximately every week (2014) or fortnightly (2015) from the vegetative stage to the pod filling stage in 2014 and 2015.…”
Section: Measurementsmentioning
confidence: 99%
“…Non-destructive measurements of canopy reflectance, from which Normalised Difference Vegetation Index (NDVI) was calculated, were taken with a CropCircle ACS-210 with GeoSCOUT GLS-400 data logger (Holland Scientific, Lincoln, NE, USA) as an indirect measurement of crop canopy development (Fitzgerald, 2010;Perry et al, 2012). These were taken approximately every week (2014) or fortnightly (2015) from the vegetative stage to the pod filling stage in 2014 and 2015.…”
Section: Measurementsmentioning
confidence: 99%
“…In addition, precise LAI measurements require plant destruction in order not to overestimate the LAI in dense canopies [19]. The NDVI can also be used to approximate fractional canopy coverage but is not a useful substitute for above-ground biomass measurements [20]. Ma et al [8] reported that plant density had no effect on the yield and NDVI relationship during the soybean reproductive growth stages.…”
Section: Introductionmentioning
confidence: 99%
“…The sensor was held ~0.5 m above the crop canopy and oriented to measure a foot-print across the middle rows of the plot. The NDVI is calculated directly by the sensor, and mean values of transects from non-disturbed areas within the subplot were used as a surrogate for canopy cover (Perry et al 2012).…”
Section: Normalised Difference Vegetation Indexmentioning
confidence: 99%